(untitled) (Review of Croatian History, 2021)
Due to the production of food and cattle fattening, the Slavonian and Srijem peasants were in the centre of interest of both the state authorities and the partisan movement during the Second World War. Both sides were very preoccupied with finding a way to win them over or force them to give the surplus to one or the other. Unwillingness to cooperate with the state authorities and partisans put the peasant’s both life and property in danger. Sowing, harvesting and other agricultural work were often only possible with an armed escort. The wheat harvests in the Slavonian and Srijem fields in 1942, 1943 and 1944 was followed by the destruction of crops, i.e. burning of wheat and the destruction of threshers. Despite such conditions, the local population managed to meet their needs, and therefore there was no famine. Due to the destruction of transport infrastructure and means of transport, in attacks by partisans and later by the Western Allies’ air force, it was difficult to transport the collected food. The population of Slavonian cities, especially workers and low-income civil servants, were in a difficult position due to irregular and scarce supplies in approvisations; and therefore, they were forced to purchase the basic foodstuffs on the “black market” at extremely high prices. The daily life became even more difficult in 1944 due to air strikes by the Western Allies and the Red Army air force. The paper gives a brief overview of these issue in the cities, mostly with examples from Brod na Savi / Slavonski Brod, and as for rural areas, mostly with examples from the mountain areas and to a lesser ex-tent from the plains, eastern Slavonia and Srijem.